Development of a Centrifuge for High -Speed Centrifugal Extraction of Moisture from Macerated Water Hyacinth - Calilung, Edwin J. (Philippine Engineering Journal; Vol 19 No 2 (1998), 2021)
Rapid mechanical dewatering of fibrous vegetative materials like water hyacinth requires separation of the process into two steps of maceration (cell breakage) and moisture extraction, to allow individual optimization for speed and efficiency. To fulfill the second step, centrifugal moisture extraction was explored. Centrifugal moisture extraction characteristics were determined using a fabricated batch loading centrifuge to determine its potential for rapid moisture extraction. A continuous-loading conical centrifuge was designed, fabricated and tested for continuous high-capacity moisture extraction from macerated of water hyacinth. Batch centrifuge tests were conducted to establish the performance parameters for centrifugal moisture expression from macerated water hyacinth. The tests showed the following basic trends: • Percent moisture extraction, weight reduction, and vegetable matter loss significantly increased with increasing degree of maceration. • Percent moisture extraction, weight reduction, and vegetable matter loss increased as centrifugal acceleration was increased. • Percent moisture extraction, weight reduction, and vegetable matter loss increased with increasing spin duration. Moistures and weight reduction were observed to exponential functions of spin duration and a critical spin duration of 5 seconds was determined for all treatments. Moisture and weight reduction were also found to be linear function of centrifugal acceleration. Little change, however, resulted from increasing levels of centrifugal acceleration. Greater moisture and weight reduction resulted from increasing degree of maceration (through extrusion in a die ring with small hole diameter or several maceration passes). The target moisture reduction was attained as a centrifugal acceleration of 1341-g, 5seconds spin duration and with the hyacinth macerated in a 6.35 mm die ring or twice macerated in a 12.70 mm die ring. To achieve higher throughput and better efficiency, a cone type continuous-loading centrifuge was designed, constructed and tested. The prototype, however, did not function properly due to the inherent difficulty on controlling the flow off fibrous macerated material up the conical screen surface. The material tended to form a mat that was difficult to break and which remained fixed in the cone surface. A system for controlled and positive displacement of the material along the conical screen surface should solve the problem, but will complicated the design, require high fabrication tolerances and increase machine costs considerably.